TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Downscaling and visioning of mountain snow packs and other climate change implications in North Vancouver, British Columbia - Stewart Jay Cohen; Stephen Sheppard; Alison Shaw; David Flanders; Sarah Burch; Bill Taylor; David Hutchinson; Alex Cannon; Stuart Hamilton; Brent Burton; Jeff Carmichael (Mitigation and Adaptation Strategies for Global Change, 2012)

Incorporating climate change adaptation into national conservation assessments - EDWARD T GAME; GEOFFREY LIPSETT‐MOORE; EARL SAXON; NATE PETERSON; STUART SHEPPARD (Global Change Biology, 2011)
The Convention on Biological Diversity requires that member nations establish protected area networks that are representative of the country's biodiversity. The identification of priority sites to achieve outstanding representation targets is typically accomplished through formal conservation assessments. However, representation in conservation assessments or gap analyses has largely been interpreted based on a static view of biodiversity. In a rapidly changing climate, the speed of changes in biodiversity distribution and abundance is causing us to rethink the viability of this approach. Here we describe three explicit strategies for climate change adaptation as part of national conservation assessments: conserving the geophysical stage, identifying and protecting climate refugia, and promoting cross‐environment connectivity. We demonstrate how these three approaches were integrated into a national terrestrial conservation assessment for Papua New Guinea, one of the most biodiverse countries on earth. Protected areas identified based on representing geophysical diversity were able to capture over 90% of the diversity in vegetation communities, suggesting they could help protect representative biodiversity regardless of changes in the distribution of species and communities. By including climate change refugia as part of the national conservation assessment, it was possible to substantially reduce the amount of environmental change expected to be experienced within protected areas, without increasing the overall cost of the protected area network. Explicitly considering environmental heterogeneity between adjacent areas resulted in protected area networks with over 40% more internal environmental connectivity. These three climate change adaptation strategies represent defensible ways to guide national conservation priority given the uncertainty that currently exists in our ability to predict climate changes and their impacts. Importantly, they are also consistent with data and expertise typically available during national conservation assessments, including in developing nations. This means that in the vast majority of countries, these strategies could be implemented immediately.